ANALISIS NILAI NILAI TAJIMUL ILMI WA AHLIHI PADA KITAB TALIM MUTA'ALIM - Fitria, Ighna; Atqia, Wirani (Rabbani: Jurnal Pendidikan Agama Islam, 2023)
The characters taught in education in Indonesia lack the value of faith and the concept of adab. As a result, the education system in Indonesia is experiencing moral decline. Teachers strive to instill noble values in the minds of students so that they have noble values and are able to avoid wrong actions. Literature review is combined with a qualitative approach in this research. In this study, the researcher is the most important instrument. The translation of Ta'lim Al-Muta'allim became the data source. Data reduction, data presentation, and data verification are the methods used in data analysis. The findings of this study can be found in the one of the chapters of the book, which provide information on the eight values of moral education and give a strong emphasis on the idea of manners and its influence on the morals of students and teachers in Islamic Religious Education.